PELAKSANAAN PEKERJAAN STRUKTUR ATAS DENGAN BETON PRACETAK PADA PROYEK GEDUNG - Sri Haryati; Andrias Rudi Hermawan (Politeknik Negeri Jakarta, 2021)
The implementation of upper structure works in the BPJS Kesehatan Jakarta Pusat building project, using conventional reinforced concrete in the process which requires a long time. However, the needs for constructing a BPJS building service center encourages effective and efficient methods of carrying out structural work in terms of timeliness, practicality, strength, and stability of the structure. Precast reinforced concrete structures as an alternative technology in carrying out structural work have several advantages over conventional reinforced concrete. The main differences are the connection, concrete quality, and erection; significantly related to the cost and time of implementation. This study aims to calculate the connection using the wet connection system, analyze aspects of cost, quality, time, and work implementation of the use of precast reinforced concrete by making comparisons using conventional reinforced concrete in the BPJS Kesehatan Jakarta Pusat building project. This research was conducted by analyzing the method of carrying out structural work on precast concrete. The data needed is in the form of unit yard prices, Standard Operating Procedures for implementing precast concrete works, unit prices for precast concrete products. Data collections are done by direct observation and interview with Project Manager. Calculation of distribution length for precast concrete joints refers to SNI 2847: 2013 while the cost of precast concrete refers to SNI 7832: 2017. The results of the study stated that lap-splice (ld) for the 420 mm beam-beam connection of 228 mm hooks, 320 mm beam of 228 mm hooks, between the plates of 150 mm, columns of 880 mm; the cost decreased 25,43% compared to conventional concrete; precast concrete takes 56 days, 7 days faster or 11,11% compared to conventional concrete. Keywords: Precast Concrete, Implementation Method, Joint, Cost and Time.